Tingkat Kecemasan Perawat dalam Menangani Pasien Covid-19 di Wilayah Kabupaten Blora - Dwi Juliantina; Epi Saptaningrum; Nella Marsela; Nunuk Wahyu Astuti; Nia Dwi Astuti; Ajeng Titah Normawati (Jurnal Studi Keperawatan, 2023)
Nowadays, the world is still at the time of the COVID-19 pandemic, where cases are still increasing every day. Nurses as the front line in treating COVID-19 patients have a major role in providing direct services to patients. Therefore, nurses are at high risk of dealing with psychological conditions such as anxiety. Nurses who are directly involved in handling and treating COVID-19 patients are at risk of experiencing psychological issues. Method: This research is descriptive research using a cross-sectional with a survey via google form. The population in this research were nurses at Three Blora District Hospitals, they are  RSUD Dr. R. Soetijono Blora, RSU Permata Blora, and RSUD Dr. R. Soeprapto Cepu. Researchers will use a sample of 20 nurses in each hospital. Results: The results of the analysis of the data collected from the 40 COVID-19 nurses revealed that 52,5% of the respondents experienced mild anxiety; 27,5% had moderate anxiety; 10% had severe anxiety; while 10% did not experience any anxiety. Covid-19 nurses who are women, 35-45 years old, Diploma Three of Nursing tend to have higher levels of anxiety. Conclusion: Marital status, hospital support and depression levels are the factors that affect the level of anxiety among COVID-19 nurses in hospitals. Hospital support is a significant factor affecting anxiety levels.Keywords: Covid-19, Nurses, Anxiety.